2021
DOI: 10.3390/ijms22115731
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Biomimetic Peptide Modification of Alginate: Efficiency, Side Reactions, and Cell Response

Abstract: In the fast-developing field of tissue engineering there is a constant demand for new materials as scaffolds for cell seeding, which can better mimic a natural extracellular matrix as well as control cell behavior. Among other materials, polysaccharides are widely used for this purpose. One of the main candidates for scaffold fabrication is alginate. However, it lacks sites for cell adhesion. That is why one of the steps toward the development of suitable scaffolds for cells is the introduction of the biofunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In general, for the conjugate and free pigment, the proton chemical shifts assigned to the structure of Pyflav-CHT 6 did not alter significantly except for the two singlets assigned to H-3 and H-9 which slightly undergo downfield shifts. The peaks with higher chemical shift (δ 4.83 ppm) in the sodium ALG region were assigned to the guluronic acid anomeric proton (H-4G) in agreement with data previously reported in the literature. , The acquired NMR spectra also allowed the determination of substitution of pigment 5 in ALG to be 1.2%, from the ratio between of the peak integrals corresponding to H-3″ and H-5″ protons of pigment (6.80 ppm) and the one at 4.83 ppm that corresponds to proton H-4G in ALG, as shown in eq …”
Section: Results and Discussionsupporting
confidence: 89%
“…In general, for the conjugate and free pigment, the proton chemical shifts assigned to the structure of Pyflav-CHT 6 did not alter significantly except for the two singlets assigned to H-3 and H-9 which slightly undergo downfield shifts. The peaks with higher chemical shift (δ 4.83 ppm) in the sodium ALG region were assigned to the guluronic acid anomeric proton (H-4G) in agreement with data previously reported in the literature. , The acquired NMR spectra also allowed the determination of substitution of pigment 5 in ALG to be 1.2%, from the ratio between of the peak integrals corresponding to H-3″ and H-5″ protons of pigment (6.80 ppm) and the one at 4.83 ppm that corresponds to proton H-4G in ALG, as shown in eq …”
Section: Results and Discussionsupporting
confidence: 89%
“…Many efforts have been made to induce an appropriate cellular adhesion in alginate gels. Besides the introduction of gelatin or collagen in the ink [ 16 ], one strategy is to graft different cell adhesive peptides to alginate [ 34 , 35 ]. Recently, Criado-Gonzalez and coworkers [ 36 ] showed that the incorporation of a self-assembled phosphorylated tri-peptide, Fmoc-FFY (Fmoc: 9-fluorenylmethoxycarbonyl; F: phenylalanine; Y: tyrosine), within the polyethylene glycol [ 37 ] or hyaluronic acid hydrogels allowed for the promotion of fibroblast cell adhesion [ 36 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…72,73 DMTMM and corresponding reactive ester intermediates are soluble and more stable against hydrolysis, compared to those based on EDC, therefore enabling more effective amide bond formation in a variety of protic solvents. 47,74 Though DMTMM has been used for amidation in a wide range of systems (e.g. to enable ''grafting to'' of free polymer chains onto surfaces, molecular polymer brushes and free polymer chains), [75][76][77][78] only a few recent reports have explored this approach for the functionalization of surfacetethered polymer brushes.…”
Section: Reactive Esters For Amide Bond Formationmentioning
confidence: 99%